2021
DOI: 10.48550/arxiv.2112.11079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data fission: splitting a single data point

Abstract: Suppose we observe a random vector X from some distribution P in a known family with unknown parameters. We ask the following question: when is it possible to split X into two parts f (X) and g(X) such that neither part is sufficient to reconstruct X by itself, but both together can recover X fully, and the joint distribution of (f (X), g(X)) is tractable? As one example, if X = (X1, . . . , Xn) and P is a product distribution, then for any m < n, we can split the sample to define f (X) = (X1, . . . , Xm) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Then, U ∼ N n (θ, (1+γ)I n ) and V ∼ N n (θ, (1+γ −1 )I n ) are independent. Rasines & Young (2022) and Leiner et al (2022) applied this decomposition to address Scenario 1 in Section 1. Additionally, Rasines & Young (2022) showed that this leads to asymptotically valid inference under certain regularity conditions, even when X is not normally distributed.…”
Section: Thinning Natural Exponential Families Into Natural Exponenti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Then, U ∼ N n (θ, (1+γ)I n ) and V ∼ N n (θ, (1+γ −1 )I n ) are independent. Rasines & Young (2022) and Leiner et al (2022) applied this decomposition to address Scenario 1 in Section 1. Additionally, Rasines & Young (2022) showed that this leads to asymptotically valid inference under certain regularity conditions, even when X is not normally distributed.…”
Section: Thinning Natural Exponential Families Into Natural Exponenti...mentioning
confidence: 99%
“…Our generalized thinning framework achieves the goal set out in their paper, providing a concrete recipe for finding such decompositions in a broad set of examples. Another paper with a similar goal is Leiner et al (2022). They define "data fission", which seeks to find random variables f (X) and g(X) for which the distributions of f (X) and g(X) | f (X) are known and for which X = h(f (X), g(X)).…”
Section: Introductionmentioning
confidence: 99%